The new Hispanic American witch hunt: the case of Witches by Brenda Lozano and Hurricane Season by Fernanda Melchor (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2024)
Since the last decade, the fourth wave of the feminist movement has taken the figure of the witch as its standard bearer, and the character has been updated and vindicated. What were once depraved women who lived on the fringes are now the object of the admiration and respect of their peers. As a reflection of what happens in reality, Fernanda Melchor and Brenda Lozano show us through their works the life and death of two female characters with non-normative corporealities whose situation was negatively added to by the fact that they were considered shamans or witches within their communities. In this article we will look at the possible relationship between the Western and Mexican traditions, which together create a new type of magic within the social imaginary. To this we will add the way in which the narrative is configured to show how social vulnerability influences the violence to which these women will fall victim.